Detection of colorectal cancer and advanced neoplasia during first surveillance interval after detection of adenomas in fecal immunochemical test cancer screening: a nationwide study - Larsen, Pernille T.; Jørgensen, Susanne F.; Hagemann-Madsen, Rikke; Rasmussen, Morten; Andersen, Berit; Njor, Sisse H. (Endoscopy, 2024)
Background Adenoma surveillance guidelines are based on non-fecal immunochemical test (FIT)-based screening settings. However, colorectal cancer (CRC) risk may be different in FIT-positive screening populations. We evaluated the CRC and advanced adenoma risk within the recommended surveillance periods in the Danish FIT-based CRC screening program for participants with intermediate or high risk adenomas according to 2010 European guidelines. Furthermore, we estimated CRC risk for those who were not recommended surveillance according to European Society of Gastrointestinal Endoscopy (ESGE) 2020 guidelines.Methods Using nationwide health registries, we identified 17 936 FIT-screening participants from 2014–2017 with adenomas undergoing surveillance (high risk 1 year, intermediate risk 3 years). Participants with a follow-up examination were included (N = 10 068). Relative risk (RR) of CRC and advance adenoma was compared between intermediate and high risk groups and between intermediates who were recommended surveillance (S) or no surveillance (NS) according to 2020 ESGE guidelines.Results During surveillance, CRC occurred in 0.59% of the high risk group and 1.11% of the intermediate risk group (RR 0.53 [95%CI 0.34–0.84]). The high risk group had a 24% increased risk of advanced adenoma. CRC occurred in 1.69% of the intermediateNS group and 0.87% of the intermediateS group (RR 1.94 [95%CI 1.18–3.21]), and RR for advanced adenoma was 1.19 (95%CI 1.03–1.37).Conclusion CRC detection was lower among participants rated at higher risk at initial CRC screening. Findings at first screen-derived colonoscopy might not be as good a predictor of CRC risk in a FIT-positive screening population.